If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16(x + 2) = 4(4x + 1) + 28 Reorder the terms: 16(2 + x) = 4(4x + 1) + 28 (2 * 16 + x * 16) = 4(4x + 1) + 28 (32 + 16x) = 4(4x + 1) + 28 Reorder the terms: 32 + 16x = 4(1 + 4x) + 28 32 + 16x = (1 * 4 + 4x * 4) + 28 32 + 16x = (4 + 16x) + 28 Reorder the terms: 32 + 16x = 4 + 28 + 16x Combine like terms: 4 + 28 = 32 32 + 16x = 32 + 16x Add '-32' to each side of the equation. 32 + -32 + 16x = 32 + -32 + 16x Combine like terms: 32 + -32 = 0 0 + 16x = 32 + -32 + 16x 16x = 32 + -32 + 16x Combine like terms: 32 + -32 = 0 16x = 0 + 16x 16x = 16x Add '-16x' to each side of the equation. 16x + -16x = 16x + -16x Combine like terms: 16x + -16x = 0 0 = 16x + -16x Combine like terms: 16x + -16x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| -20y=120 | | 6x=32-2x | | 40=18x-10x | | -3(x+5)+5x=10 | | 10x^2+7x-5=0 | | 6+x=32-x | | 9x-x=40 | | 5x+2(x+8)-6(4x-5)= | | -3x^2+7x=-10 | | 8xy+6yz-4xz-8xy= | | -47-18=13a | | -1(z-6)=-20 | | -7+8x=19x+15 | | -p=2 | | -6x+9=3x-27 | | (y+3)(y+5)= | | (3b^3+9b^2-3)+(2b^3-9b+7)= | | (15-7)x=(11+5)x | | -9=9(y+3) | | 3x+4(2-x)=4x+5 | | 4(2x)=72 | | (x^3+x^2+x+1)(5x-3)= | | 2(3+4)-6=48 | | 6x+4=24 | | 2(4x)=40 | | 9x-7+2x=8x+5-5x | | -x^2-x+2=0 | | (7x+5)(5x^2+8x+6)= | | 16x=-48 | | 0.8w-0.6+0.3w=3 | | (x^2-3x+4)(2x-1)= | | 6x+4= |